2013 IEEE International Electron Devices Meeting 2013
DOI: 10.1109/iedm.2013.6724634
|View full text |Cite
|
Sign up to set email alerts
|

Understanding the suppressed charge trapping in relaxed- and strained-Ge/SiO<inf>2</inf>/HfO<inf>2</inf> pMOSFETs and implications for the screening of alternative high-mobility substrate/dielectric CMOS gate stacks

Abstract: We study charge trapping in a variety of Ge-based pMOS and nMOS technologies, either with Si passivation and conventional SiO 2 /HfO 2 gate stack, or with GeO x /high-k gate stacks. A general model for understanding this phenomenon in alternative substrate/dielectric systems is proposed. We discuss two different approaches to pursue a reduction of charge trapping in alternative material systems, which will be necessary for achieving reliable high-mobility devices.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
43
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 47 publications
(49 citation statements)
references
References 14 publications
6
43
0
Order By: Relevance
“…1,2,4,6,15,19,20 The benefit of the Si passivation layer above GeO x -based gate stacks is its potential to improve Bias Temperature Instability (BTI) reliability. 4,36 It is important to avoid surface segregation of Ge through the Si layer during the epitaxial growth as this leads to an increase of the interfacial trap density and distribution in the finalized gate stack. 20 On the other hand, the Si passivation layer has to be sufficiently thin to approach an Equivalent Oxide Thickness (EOT) close to 1 nm as implemented in the current 14 nm-node Fin-FET.…”
Section: In Ref 2)mentioning
confidence: 99%
“…1,2,4,6,15,19,20 The benefit of the Si passivation layer above GeO x -based gate stacks is its potential to improve Bias Temperature Instability (BTI) reliability. 4,36 It is important to avoid surface segregation of Ge through the Si layer during the epitaxial growth as this leads to an increase of the interfacial trap density and distribution in the finalized gate stack. 20 On the other hand, the Si passivation layer has to be sufficiently thin to approach an Equivalent Oxide Thickness (EOT) close to 1 nm as implemented in the current 14 nm-node Fin-FET.…”
Section: In Ref 2)mentioning
confidence: 99%
“…It has been speculated that the degradation in GeO 2 /Ge device is caused by hole trapping at low energy levels [8]. However, detailed information of these hole traps, such as the energy distribution, the differences from those in Si devices, and their corresponding degradation kinetics, have not been discussed.…”
Section: Introductionmentioning
confidence: 99%
“…Both are deposited on top of the Ge channel. With the Si-capped device it has been reported that bias induced degradation can be lower than its Si counterpart [8]. GeO 2 /Ge devices, on the other hand, offer higher mobility for both p and n MOSFETs [9].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…[5][6][7][8][9] Si-passivation is advantageous over GeO xbased gate stack in terms of Bias Temperature Instability (BTI) reliability. [10][11][12][13][14] Ge surface segregation during the epitaxial Si growth needs to be avoided as it leads to an increase of the interfacial trap density and distribution in the final gate stack. 10,15,16 On the other hand, the Si passivation layer has to be sufficiently thin.…”
mentioning
confidence: 99%